Africa RISING in Malawi: Impact brief - Azzarri, Carlo; Boukaka, Sedi Anne; Vitellozzi, Sveva (International Food Policy Research Institute, 2023)
Interventions/Innovations The Africa RISING (AR) program in Malawi was implemented in Dedza and Ntcheu districts in the country’s Central region, primarily using an on-farm participatory approach. The program supported cropping system improvements through promotion of improved varieties and quality seeds for beans, soybeans, groundnuts, and pigeon peas. It also aimed to foster the adoption of sustainable and productivity enhancing practices (e.g., legume legume or maize-legume intercropping and consistent grain-legume rotation) and nutrient cycling for soil enrichment (e.g., building soil organic matter, implementing a rainfall responsive nitrogen fertilization strategy). Livestock interventions focused primarily on supplementary feeding of goats to promote animal health and weight gain. Increased agricultural productivity and the processing of more nutritious grain legumes were considered prime channels for improving household income, diet diversity, and overall nutrition.